2007
DOI: 10.1089/lap.2006.0073
|View full text |Cite
|
Sign up to set email alerts
|

The Deflux Procedure Reduces the Incidence of Urinary Tract Infections in Patients with Vesicoureteral Reflux

Abstract: We conclude that the Deflux procedure is effective not only in eliminating VUR on radiologic studies, but also in reducing the incidence of UTIs and antibiotic use in children with VUR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 43 publications
6
31
0
Order By: Relevance
“…This finding is similar to that of Wadie et al, who found an E coli UTI in 82% of a post-injection group. 15 In our study, febrile UTI developed in most children (55%) in their first year, after resolution of VUR. In their series, Elmore et al have reported that UTI developed within the first year after successful treatment in 83% of children in the Dx/HA group and 86% in the open surgery group.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…This finding is similar to that of Wadie et al, who found an E coli UTI in 82% of a post-injection group. 15 In our study, febrile UTI developed in most children (55%) in their first year, after resolution of VUR. In their series, Elmore et al have reported that UTI developed within the first year after successful treatment in 83% of children in the Dx/HA group and 86% in the open surgery group.…”
Section: Discussionsupporting
confidence: 47%
“…It has been reported that female sex and bilateral VUR are risk factors for post-treatment UTI. 15 Sedberry-Ross et al stated that 9 of 12 children (75%) in the infection group had a history of dysfunctional elimination, and 9 of 12 children (75%) had multiple preoperative febrile UTIs. 9 The incidence of renal scarring was not statistically significant between the UTI and the no UTI group.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies suggest that appropriate selection of patients can lead to higher success rate, lower recurrence and complications, however biodegradable agents such as Dx/HA may cause VUR recurrence and failure during long-term follow up (25). The reported success rate is 70% for VUR correction using STING procedure in the literature (8,23). In the current study, the success rate for endoscopic correction of the VUR using Dx/HA injection was 93.3%, which provides a higher rate compared to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the success rate for endoscopic correction of the VUR using Dx/HA injection was 93.3%, which provides a higher rate compared to the literature. However, in a study by Wadie et al, the overall success rate was reported 77.4% during single Dx/HA injection (8). Several studies evaluated poly-acrylate polyalcohol copolymer (PPC) as an effective and safe material in VUR correction instead of Dx/HA and its success rate has been reported more than 90% (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation